THEORETICAL FOUNDATIONS FOR THE STUDY OF SECONDARY NOMINATION AS A METHOD OF TERMINOLOGY FORMATION (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
This article deals with the theoretical studies of the secondary nomination as a method of terminology formation . It clearly demonstrates the problem of determining and studying the main language functions